Liver glycogen synthase, phosphorylase, and the glycogen concentration in rats given a glucose load orally: A 24-hour study - (:unkn) unknown (My University, 1994)
Fasted rats were given 4 g/kg glucose orally. Synthase R (active forms), total synthase, and phosphorylase a activities, and hepatic glycogen, glucose B-phosphate (glucose-6-P), uridine diphosphoglucose (UDP-glucose), glucose, and plasma glucose concentrations were determined over the subsequent 24 h. The resulting glycogen concentration changes could be divided into three distinct phases. A glycogen synthetic phase (between 0 and 4 h), a stability phase (between 4 and 12 h), and a degradation phase (between 12 and 24 h). Synthase R activity increased rapidly and reached a maximum at 20 min. With the onset of glycogen synthesis it gradually decreased below the control values, reaching a nadir by 4 h. During the glycogen stability phase it gradually increased again up to the control value. It then remained stable during the subsequent glycogen degradation phase. Phosphorylase a activity did not change throughout the entire 24-h period. Glucose-6-P concentration increased almost twofold at 20 min. It then decreased but was above the control values at the 24th h. The plasma and hepatic glucose concentrations increased as expected after the glucose load. They then decreased but remained above the control value at all subsequent time points. In summary, the synthase R, phosphorylase a activities, or changes in the known allosteric modifiers of these enzymes could not explain the changes in glycogen concentration. The reasons for these discrepancies remain to be determined. © 1994 Academic Press.
Keywords: Glucose 6-phosphate; Glucose ingestion; Hepatic glucose; UDP-glucose